High-Frequency Chest Compression: A Summary of the Literature - Cara F Dosman; Richard L Jones (Canadian Respiratory Journal)
The purpose of the present literature summary is to describe high-frequency chest compression (HFCC), summarize its history and outline study results on its effect on mucolysis, mucus transport, pulmonary function and quality of life. HFCC is a mechanical method of self-administered chest physiotherapy, which induces rapid air movement in and out of the lungs. This mean oscillated volume is an effective method of mucolysis and mucus clearance. HFCC can increase independence. Some studies have shown that HFCC leads to more mucus clearance and better lung function compared with conventional chest physiotherapy. However, HFCC also decreases end-expiratory lung volume, which can lead to increased airway resistance and a decreased oscillated volume. Adding positive end-expiratory pressure to HFCC has been shown to prevent this decrease in end-expiratory lung volume and to increase the oscillated volume. It is possible that the HFCC-induced decrease in end-expiratory lung volume may result in more mucus clearance in airways that remain open by reducing airway size. Adjunctive methods, such as positive end-expiratory pressure, may not always be needed to make HFCC more effective.